An Estimation of X-Radiation output using mathematic model - Suchart Kothan (2018)
Problem statement: Diagnosis x-ray radiation safety is key in medical examination. The quantity of patient radiation doses is beneficial for radiation protection of the patient. It was proposed that the equation for estimating the output (milliReongent, mR) from x-ray machines. Approach: A was 0.5, 0.8 and 1.0 for single phase, three phases and high frequency x-ray machines, respectively. To compare calculated output (mR) used this equation and measured output (mR) used ionizing chamber dosimeter. Results: The difference between the calculated and measured radiation dose was quite small. Conclusion: This equation could use to estimate output and it altered the reliable and inexpensive techniques for patient dose measurement in routine diagnostic x-ray examinations. © 2011 Science Publications.